2004
DOI: 10.1111/j.1365-294x.2004.02180.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidden biodiversity of the extremophilic Cyanidiales red algae

Abstract: The Cyanidiales is a group of asexual, unicellular red algae, which thrive in acidic and high temperature conditions around hot springs. These unicellular taxa have a relatively simple morphology and are currently classified into three genera, Cyanidium, Cyanidioschyzon and Galdieria. Little is known, however, about the biodiversity of Cyanidiales, their population structure and their phylogenetic relationships. Here we used a taxonomically broadly sampled three-gene data set of plastid sequences to infer a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
216
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(231 citation statements)
references
References 34 publications
15
216
0
Order By: Relevance
“…Interestingly, Galdieria is usually found growing in endolithic or interlithic habitats (Gross et al 1998;CiNiglia et al 2004;YooN et al 2006;PiNto et al 2007), however, in Ostrava site we have found the entire rich population living on the soft substrates as are the residuals of trees. First of all, organic matter can hold water which is crucial for survival and which may be limiting in low water holding capacity having soils of the spoil heaps, especially when the coal is still burning underneath the surface.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Interestingly, Galdieria is usually found growing in endolithic or interlithic habitats (Gross et al 1998;CiNiglia et al 2004;YooN et al 2006;PiNto et al 2007), however, in Ostrava site we have found the entire rich population living on the soft substrates as are the residuals of trees. First of all, organic matter can hold water which is crucial for survival and which may be limiting in low water holding capacity having soils of the spoil heaps, especially when the coal is still burning underneath the surface.…”
Section: Discussionmentioning
confidence: 73%
“…Two MCMC runs for one million generations each with one cold and three heated chains were conducted with trees sampled every 100 generations. Maximum likelihood (ML) analysis was conducted in MEGA7 (Kumar et al 2016) with 1000 bootstrap replicates using Nearest-Neighbor-Interchange and rCR (CiNiglia et al 2004). A partial fragment of calmodulin gene (CaM) of environmental Ostrava sample 2015 and strain CCALA 965 was amplified using primers Calmo 140F and Calmo 510R (YooN et al 2006).…”
Section: Morphological Characterization Cell Morphology Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…No cell division occurs above pH 5 (Doemel and Brock, 1971). The extremely acidophilic nature of C. caldarium is a common feature of the Cyanidiaceae, a red algal group comprising six species, namely, Galdieria sulphuraria, Galdieria partita, Galdieria daedala, Galdieria maxima, Cyanidium caldarium and Cyanidioschyzon merolae (Albertano et al, 2000;Ciniglia et al, 2004). Among these, the complete genome of G. sulphuraria and C. merolae has been sequenced (Weber et al, 2004;Matsuzaki et al, 2004).…”
Section: Introductionmentioning
confidence: 99%